The Effect of Combined Fibular Reposition and Facilitatory Fibularis Longus Taping on Balance in Patients with Chronic Ankle Instability: A Randomized Clinical Trial - Katayoon Rezaei; Shohreh Taghizadeh; Amir Nejati; farahnaz emami (Shiraz University of Medical Sciences, 2024)
Background: Ankle sprains are common musculoskeletal injuries in sports and physical activities, often leading to balance impairments. The research investigated the impact of combined fibular repositioning taping (FRT) and facilitatory fibularis longus taping on postural balance and proprioception of the ankle joint in individuals with Chronic Ankle Instability (CAI). Methods:The double-blind randomized controlled trial was conducted at the Rehabilitation Sciences Research Center, Shiraz University of Medical Sciences (SUMS). A total of 40 patients aged between 18 and 50 were randomly allocated to either the intervention or placebo group. In the intervention group, participants received a combined FRT and facilitatory fibularis longus taping. In contrast, participants in the placebo group received an adhesive gauze from the medial malleolus to the midpoint of the tibia. Static and dynamic postural stability and stability limits were evaluated using the Biodex Balance SD system. Proprioception of the ankle joint was assessed using the active ankle joint repositioning test with a Biodex isokinetic dynamometer. Data within each group were compared before and immediately after taping and 48 hours after taping. Results: The comparison of static postural stability before and immediately after the taping application revealed a significant decrease within groups (P = 0.01). Additionally, there was a statistically significant difference between groups before and 48 hours after taping (P = 0.002). A significant difference was observed between groups immediately after taping (P = 0.03) for dynamic postural stability at the double leg stance position. In contrast, no significant difference was found between groups 48 hours after taping (P = 0.05). Conclusion:The results suggest that combined FRT and facilitatory fibularis longus taping could enhance static and dynamic postural stability in individuals with CAI.